Short femoral stem and porous titanium: winning combination? - Mantelli, P.; Fioruzzi, A.; Bisogno, L.; Fioruzzi, C.; Fusco, U.; Olivieri, M.; Lisanti, M. (Acta Biomedica Atenei Parmensis, 2014)
A lot of different implants are avaible in hip replacement arthroplasty (THA), stems differ mainly by type of fixation, material, length, diameter, shape, surface coating, modularity, etc. The main quality of a non-cemented stem is to pursuit primary and secondary stability, to preserve bone stock, to be adaptable and modular. The literature shows that the most popular non cemented stems used in THA are metaphyseal femoral stem in which the distal portion has only the action to avoid varus stem placement but can also be a source of complications such as stress shielding. The stability of a short stem is closely dependent on material that must allow a high “scratch fit” and facilitate osteointegration with a generous surface of bone-implant contact. From September 2010 we have performed 287 THA using a modular titanium porous short stem. The article shows the preliminary results, which are very encouraging, showing excellent primary and secondary osteointegration, also slightly undersized implants or in elderly porotic patients.